2023
DOI: 10.1007/s00603-022-03192-0
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Poroelastic Modelling of Depletion-Induced Pore Pressure Changes in Valhall Overburden

Abstract: Stress and pore pressure changes due to depletion of or injection into a reservoir are key elements in stability analysis of overburden shales. However, the undrained pore pressure response in shales is often neglected but needs to be considered because of their low permeability. Due to the anisotropic nature of shales, the orientation of both rock and stresses should be considered. To account for misalignment of the medium and the stress tensor, we used anisotropic poroelasticity theory to derive an angle-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…This indicates a globally optimized set of TOE coefficients. For D shale, we bootstrapped the inversion of the TI TOE coefficients by using subsets of experimental data including only two stress paths, resulting in six subsets, as also discussed by Duda et al (2020) with a hexagonal TOE model. Except for the subset that included the isotropic stress path and the uniaxial-strain path, all bootstrapped TOE coefficients remained within the 95% confidence interval obtained in the complete inversion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This indicates a globally optimized set of TOE coefficients. For D shale, we bootstrapped the inversion of the TI TOE coefficients by using subsets of experimental data including only two stress paths, resulting in six subsets, as also discussed by Duda et al (2020) with a hexagonal TOE model. Except for the subset that included the isotropic stress path and the uniaxial-strain path, all bootstrapped TOE coefficients remained within the 95% confidence interval obtained in the complete inversion.…”
Section: Discussionmentioning
confidence: 99%
“…This preservation technique enables the cores to be stored for a long time while retaining their suitability for subsequent testing, as it minimizes the loss of pore fluid that would otherwise cause irreversible damage to the shales. The experimental data from these shales are also discussed by Bakk, Holt, Bauer et al (2020 and Duda et al (2020). The key characteristics of the shales are summarized in Table 1.…”
Section: Methods Materials Experimental Setup and Establishment Of In...mentioning
confidence: 99%
See 2 more Smart Citations
“…For shales and similar rocks, many laboratory studies have investigated the anisotropic mechanical and hydro‐mechanical properties including the elastic constants (e.g., Kim et al., 2012; Sarout et al., 2017), the poroelastic behavior (Duda et al., 2021; Horsrud et al., 1998; Islam & Skalle, 2013), and the compressive shear strength (Ambrose et al., 2014; Attewell & Sandford, 1974; Bonnelye et al., 2017b; Chenevert & Gatlin, 1965; Horsrud et al., 1998; Ibanez & Kronenberg, 1993; Islam & Skalle, 2013; McLamore & Gray, 1967; Minardi et al., 2021; Niandou et al., 1997; Wild & Amann, 2018a). Many previous studies conducted uniaxial compressive and indirect tensile strength tests under various loading configurations (e.g., Ajalloeian & Lashkaripour, 2000; Cho et al., 2012; Debecker & Vervoort, 2009; Karakul et al., 2010) and have shown that rocks exhibit strength anisotropies.…”
Section: Introductionmentioning
confidence: 99%